2020
DOI: 10.1002/ams2.559
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral vasoconstriction syndrome: the importance of follow‐up imaging within 2 weeks

Abstract: Aim In patients with thunderclap headaches, reversible cerebral vasoconstriction syndrome (RCVS) should be considered as a differential diagnosis. However, RCVS diagnosis in the emergency department (ED) remains challenging. This report describes the clinical features and factors related to RCVS diagnosis and suggests diagnostic strategies for its management. Methods We retrospectively reviewed the medical records of eight patients diagnosed with RCVS from January 2010 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…As far as the timing of vasoconstriction is concerned in relation to symptom onset, our search of published observational studies demonstrated that visible vasoconstriction could occur on the same day as symptom onset, as has been reported by Shimoda et al [56]. There are also reports of vasoconstriction being visible 1-3 days afterward [25,31], but it is most commonly evident some days into the disease course [18,37,44,46]. According to two reviews focusing on the neuroimaging evaluation of the syndrome, the peak of vasoconstriction is around 16 days after clinical onset, and it resolves within 3 months [80,81].…”
Section: Imaging In Rcvs and Temporal Relation Of Symptomatology And ...supporting
confidence: 62%
See 1 more Smart Citation
“…As far as the timing of vasoconstriction is concerned in relation to symptom onset, our search of published observational studies demonstrated that visible vasoconstriction could occur on the same day as symptom onset, as has been reported by Shimoda et al [56]. There are also reports of vasoconstriction being visible 1-3 days afterward [25,31], but it is most commonly evident some days into the disease course [18,37,44,46]. According to two reviews focusing on the neuroimaging evaluation of the syndrome, the peak of vasoconstriction is around 16 days after clinical onset, and it resolves within 3 months [80,81].…”
Section: Imaging In Rcvs and Temporal Relation Of Symptomatology And ...supporting
confidence: 62%
“…The study hypothesized that CPV gradually progresses after the onset of RCVS, peaks at the time of TCH remission, and does not progress further afterward [57]. Fukaguchi et al also propose performing clinical and imaging follow-ups for at least 2 weeks to exclude the syndrome [31].…”
Section: Imaging In Rcvs and Temporal Relation Of Symptomatology And ...mentioning
confidence: 99%
“…The exam may result negative in more than half of the cases [ 24 ]. Therefore, Fukaguchi et al have proposed to perform clinical and imaging follow-up for at least 2 weeks to exclude the syndrome [ 25 ].…”
Section: Computed Tomographymentioning
confidence: 99%